Public Perceptions of Ethical Challenges and Opportunities for Enterprises in the Digital Age - Ahmad Mansour; Khaled Alshaketheep; Hind Al-Ahmed; Ahmad Shajrawi; Arafat Deeb (Ianna Journal of Interdisciplinary Studies)
Background: Contemporary organisations are surrounded by more problematic ethical challenges due to the growing role of supercomputers in society, striving to harmonize organisational processes with ethical and technological solutions. These challenges relate broadly to the nature of technological advancements in the use of digital technologies and their associated ethical implications.